The study of diversity and distribution of bats in several fragmented forests and small adjacent islands in Batam City, Riau Island, Indonesia - FAUZIAH SYAMSI; WILSON NOVARINO; DAHELMI DAHELMI; CHAIRUL CHAIRUL (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Syamsi F, Novarino W, Dahelmi, Chairul. 2025. The study of diversity and distribution of bats in several fragmented forests and small adjacent islands in Batam City, Riau Island, Indonesia. Biodiversitas 26: 223-232. Bats are ecologically and taxonomically diverse and crucial in tropical ecosystems, including on islands. This study compares bat diversity in fragmented forests on urban islands and adjacent islands connected by bridges to assess the impact of urbanization on bat populations, providing insights for conservation and habitat management. We sampled bats across four sites in Batam City, Indonesia, including two secondary forests (SF1 and SF2) and two small islands (SI1 and SI2). Using 120 harp trap nights and 120 net nights, we captured 429 bats representing 15 species and 4 families. Our findings revealed moderate bat diversity (H' 1.02 to 1.66), with SF1 being the most stable habitat, showing balanced species richness, evenness (0.72), and low dominance (0.24), indicating an evenly distributed community. The Bray-Curtis Similarity index indicated that SF1 had a distinct bat community with only 58% similarity to other habitats. Notably, two near-threatened species were found in SF1, emphasizing its ecological significance. The study suggests that fragmented forests with healthy vegetation and habitat complexity surrounding urban areas are more supportive of bat populations than small islands with limited resources. These results highlight the need for targeted conservation efforts in forest fragments surrounding urban areas to preserve bat diversity in Batam City, Riau Island, Indonesia.